2020
DOI: 10.1167/iovs.61.6.13
|View full text |Cite
|
Sign up to set email alerts
|

Prostaglandin F2α Agonists Negatively Modulate the Size of 3D Organoids from Primary Human Orbital Fibroblasts

Abstract: To elucidate the molecular etiology of deepening of the upper eyelid sulcus (DUES) induced by prostaglandin (PG) analogs, a three-dimensional (3D) tissue culture system was employed using human orbital fibroblasts (HOFs). METHODS. During adipogenesis, changes in HOF 3D organoid sizes, as well as their lipids stained by BODIPY and expression of the extracellular matrix (ECM) by immunolabeling and/or quantitative PCR, were studied in the presence or absence of either 100-nM bimatoprost acid or 100-nM prostagland… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
120
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 58 publications
(132 citation statements)
references
References 51 publications
12
120
0
Order By: Relevance
“…Furthermore, these 3D culture techniques may have some limitations in terms of mimicking the physiological and pathological conditions because of the presence of an unnecessary scaffolds. Alternatively, our group recently developed a 3D cell drop culture system in which no scaffold is required 25 27 . Using this technique, we were able to obtain 3D organoids from HOF in patients with TAO using a drop culture method, and found that HIF2A played a critical role in mediating LOX-dependent ECM accumulation 25 .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Furthermore, these 3D culture techniques may have some limitations in terms of mimicking the physiological and pathological conditions because of the presence of an unnecessary scaffolds. Alternatively, our group recently developed a 3D cell drop culture system in which no scaffold is required 25 27 . Using this technique, we were able to obtain 3D organoids from HOF in patients with TAO using a drop culture method, and found that HIF2A played a critical role in mediating LOX-dependent ECM accumulation 25 .…”
Section: Discussionmentioning
confidence: 99%
“…Using this technique, we were able to obtain 3D organoids from HOF in patients with TAO using a drop culture method, and found that HIF2A played a critical role in mediating LOX-dependent ECM accumulation 25 . More recently, to elucidate the molecular etiology of DUES induced by PGs, we employed this 3D culture system using HOF and 3T3-L1 cells, and found that PGs significantly suppressed 3D organoid sizes, and modulated the spatial distribution of several ECMs surrounding the 3D organoids 26 , 27 . We therefore concluded that our developed 3D cell culture would be suitable for investigating the molecular etiology of TAO and DUES and also will be applicable for use in many other cells and organs.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In fact, quite recently, such 3D tissue cultures have been used in conjunction with several human disease models 14 . Using the 3D organoid culture technique, in our previous studies, we found that PGF2α significantly affected adipogenesis and the extracellular matrixes (ECMs) in 3T3-L1 cells 16 as well as human orbital fibrobrasts (HOFs) 17 . Therefore, in the current study, using a replicated pathogenic DUES model by 2D and 3D cultures using 3T3-L1 cells, we analyzed and compared the effects of FP and EP agonists, OMD and butaprost (Buta), on adipogenesis, ECM expression, and the sizes and physical properties of the 3D organoids.…”
mentioning
confidence: 99%